Transnational Networks in International Trade: An Evalution of Ethnicity and Culture in U.S. Trade Flows - Rosier, Kevin (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper tests the hypothesis that when two countries participate in the same transnational ethnic or cultural network, the volume of trade between them increases. Using the gravity model of international trade and data on the United States in 2000, we find that while older ancestral groups do not influence bilateral trade flows, a one-percentage increase in the foreign-born population increases bilateral trade by at least 9 percent. We also conclude that the linguistic composition of the country positively influences its trade flows. Finally, we apply these empirical findings to the current debate on U.S. immigration policy.